PENGARUH PEMBERIAN RENDAMAN GIBERELIN (GA3) PADA PEMATAHAN DORMANSI KEMIRI (Aleurites moluccana) - Sri Hartini, Kansih; Sri Rejeki Sitorus, Astri (Jurnal Biogenerasi, 2024)
Aleurites moluccana is a type of plant that can be utilized for pulp and matchsticks, as traditional medicine, cosmetic ingredients, cooking spices, charcoal, wood supply materials for industry, forest and land rehabilitation activities, preventing erosion, improving environmental quality and regulating water management. The problem in generative propagation of Aleurites moluccana is slow germination due to its hard seed coat. The purpose of this study was to identify the effect of gibberellin soaking on the germination of Aleurites moluccana seeds and to obtain information on the effective soaking time of Aleurites moluccana in gibberellin to break seed dormancy. The design used was a non-factorial Completely Randomized Design (CRD) with 5 treatments, namely no soaking (A0), soaking for 24 hours (A1), soaking for 48 hours (A2), soaking for 72 hours (A3), soaking for 96 hours (A4) with 5 replications. The results showed that Aleurites moluccana seeds gave a real effect on the parameters of germination uniformity, germination rate, germination percentage, and plant height. A good and optimal results were found in soaking for 48 hours.